Predicting Agricultural Sciences Students’ Media Literacy in a Post-Truth Era - Abigail Durheim; Kasey Harmon; Taylor Ruth; Cara Lawson (Journal of Human Sciences and Extension)
As more individuals turn to various forms of online media to seek information, misinformation and skepticism are on the rise when considering news media. Media literacy, or how individuals evaluate information they see in the news media, is critical to addressing this growing problem. This study aimed to explore the predictors of agricultural sciences students’ perceived news media literacy to gather preliminary data around this topic. Through an online survey, students enrolled in an agricultural communication class at the University of Nebraska-Lincoln completed a literacy reflection assignment. Students were asked to answer questions about their news media use, perceived media literacy, perceived value of media literacy, trust in the media, and need for cognition (NFC). Researchers found that most respondents were getting their news from social media and believed they were media literate, despite possessing low levels of trust in the media. However, NFC was the only predictor of perceived media literacy, which indicated that educators should account for NFC when developing media literacy curricula for formal and informal settings. Future research should replicate this study with a larger sample and broader population to better generalize these findings and develop solutions to the media literacy crisis in America.